What future model for international sports events? The case of the arctic winter games. Issue 1 (2nd January 2023) - Fuchs, Julien
Abstract: This article focuses on the Arctic Winter Games (AWG) that, since 1970, have been bringing together young people from across the circumpolar world. This sporting and cultural gathering prioritises sharing and exchange between young people and promotes indigenous cultural and sporting practices (Dene Games, Arctic sports). As such, the Games' purpose is to contribute to building an Arctic community. Furthermore, via their educational objectives and social aims, they assert their role as an actor in the development of the territories. This article proposes an analysis of the 2016 Games organised in Nuuk (Greenland). By employing an ethnographic approach, combining work on the archives of the AWG and interviews with participants and Games officials, we show that beyond their sporting aspect, it would seem that these events can constitute levers of social, cultural and educational development for a territory from a sustainable and responsible perspective. They thus disseminate a model that questions, even destabilises, the contemporary sports movement, while suggesting perspectives for its evolution. By examining the public value of the AWG, we will discuss the paradigm on which international sports events are built today.